KAJIAN KONSERVASI BANGUNAN MELALUI UNSUR PEMBENTUK ARSITEKTUR DALAM UPAYA PELESTARIAN BANGUNAN TUA DI KOTA BANDUNG, Studi Kasus : Gedung Panti Karya, Jalan Merdeka no. 39 Bandung, Jawa Barat: https://doi.org/10.25124/idealog.v4i1.1628 - Rahadian, Raden Gurmilang Nur (Universitas Telkom, 2019)
City of Bandung is known as a city that has many historical heritage buildings. City of Bandung’s imageas a city of Art Deco needs to be treasuredand maintained as it is known worldwide as a point of interest which drivepeople from around the world to visit and study it. As time goes, modernization concentratingon economic development often presents a threat to historic old buildings in the city of Bandung. One of the impact of this dynamicdevelopment is the potential loss of historical heritage as an object of tourism,therefore, conservation efforts should be done accordingly. One of the effortis strategic approach in developing and improving tourism, especially in the city of Bandung, namely through the preservation of old buildings. The presentation in this study focuses on building conservationstudybya case study of Panti Karya Building located on Jalan Merdeka Number 39 Bandung West Java. The research method used for analysisis the qualitative method using architectural forming elements and building studies in the composition of triadic functions-forms-meanings. The findings of this study statedthat the Panti Karya Building has strongerModern Architecturecharacteristics rather than Art Deco Architecture. The value of preserving the architecture of Panti KaryaBuilding is described according to Bandung City Regulation No.19 of Year 2009 concerning Management of Cultural Heritage Areas and Buildings includingHistorical value–the third highest building of Southeast AsianWorkers' Union and also as a pioneer of post-independence development;Architectural value–the style of Modern Architecture that shows the spirit of independence;The value of science–the style of Modern Architecture represents the progress of science andtechnology;Social culturalvalues–as a place for socializing and holding cultural performances;lastly, Building age–63 years oldof agemakes this building worthy of being categorized as a cultural heritage building